Role of Percutaneous Septal Ablation in Hypertrophic Obstructive Cardiomyopathy - Hasan, ATM Iqbal; Ahsan, SA; Rahman, AKM F; Ahmed, CM; Safiuddin, M; Hoque, Md Harisul; Habib, Ahsan; Parvin, Tanjima; Salim, Abu; Sheikh, Naveen; Arzu, Jahanara; Mahmood, Manzoor; et al. (University Heart Journal, 2013)
HCM is a relatively common genetic mediated primary cardiac disease which may cause sudden death in the young including competative athlets.PTSMA is an alternative therapeutic option for surgical septal myomectomy who are high risk for surgery and presented with severe disabling symptoms due to marked LV outflow obstruction. PTSMA is performed by injection of 1 to 4 ml of 96% to 98% ethanol into the target artery in 0.5 to 1.0 ml aliquots at 1 ml/min. Selection of patients for PTSMA includes those with severe symptoms refractory to maximum medical management associated with LV outflow gradient > 50 mm Hg and basal septal thickness > 18 mm. Successful outcome following septal ablation by LV outflow gradient often reduced to < 20 mm of Hg and improved from symptomatic standpoint. DOI: http://dx.doi.org/10.3329/uhj.v8i2.16083 University Heart Journal Vol. 8, No. 2, July 2012